Two Factor Authentication Sistem Inventarisasi Barang dan Manajemen Dana Bantuan Operasional Sekolah Dinas Pendidikan Nasional - Neneng Nuryati; Carolina Magdalena Lasambouw; Djoni Djatnika; Linda Lina Meilinda; Farida Agoes; Muhammad Rizqi Sholahuddin; Maisevli Harika (Building of Informatics, Technology and Science (BITS), 2022)
Inventory of goods at large institutions is a complicated activity; one solution is to create a structured web application system that can be accessed anywhere. At the National Education Office, it is not only inventory management that is a problem but also the management of the School Operational Assistance Fund (BOS). Data security must be a priority because it involves significant funds and can be misused by irresponsible parties. This study aims to apply Two Factor Authentication to the Goods Inventory System and BOS Fund Management. The first stage is verification by the DISDIKNAS admin at each level of education. Next, a verification email will be sent to the registrant for verification. The results showed that the use of 2FA did not interfere with the performance of the web-based application or its users. The approval rate for the system is 97.4%. This research contributes to the implementation of website security and can be applied to similar systems